2005
DOI: 10.1161/01.hyp.0000168945.44069.aa
|View full text |Cite|
|
Sign up to set email alerts
|

Ramipril Reduces Large-Artery Stiffness in Peripheral Arterial Disease and Promotes Elastogenic Remodeling in Cell Culture

Abstract: Abstract-Ramipril improves cardiovascular outcome in patients with peripheral arterial disease; however, the precise mechanisms of benefit remain to be elucidated. The effect of ramipril on large-artery stiffness in patients with peripheral arterial disease was examined. In addition, we determined the effect of ramiprilat on extracellular matrix from human aortic smooth muscle cell culture. Forty patients with peripheral arterial disease were randomized to receive ramipril, 10 mg once daily or placebo for 24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 59 publications
4
40
1
4
Order By: Relevance
“…The effect of Ile-Pro-Pro and ValPro-Pro seems to be related to ACE-inhibitory activity (Ahimastos et al, 2005;Ló pez-Fandiño et al 2006;Hong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Ile-Pro-Pro and ValPro-Pro seems to be related to ACE-inhibitory activity (Ahimastos et al, 2005;Ló pez-Fandiño et al 2006;Hong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin Ⅱ stimulates vascular smooth muscle cells (VSMCs) to generate intracellular superoxides and inflammatory cytokines and induced vascular remodeling through VSMC hypertrophy and proliferation, increased collagen synthesis and increased production of MMP [26,27] . Inhibition of the RAAS with angiotensin converting enzyme inhibitors (ACEI) or angiotensin Ⅱ receptor blockers is associated with reduction of arterial stiffness, but it is accompanied with blood pressure reduction [28,29] . In hemodialyzed patients, treatment with ACEI blood pressure lowering combined with decreased aPWV was associated with reduced all-cause and cardiovascular mortality [30] .…”
Section: Arterial Stiffness In Chronic Kid-ney Diseasementioning
confidence: 99%
“…[20][21][22] Mostly, all these disorders may be attenuated by chronic ACEI treatment. 23,24 Thus, such results taken together suggest that a more active drug therapy should be quite relevant to consider in subjects with systolic hypertension and target organ damage, particularly those with PAD. Other studies report bad blood pressure control in patients in secondary prevention; after a major cardiovascular event, the EUROASPIRE II 25 survey showed that 'only' half of the population (including normotensives and hypertensives) had normal BP.…”
Section: Discussionmentioning
confidence: 97%